Ethnopharmacological Study on Traditional Knowledge of Medicinal Plant Used from Secondary Forest in Community at Sekabuk Village, Mempawah District, West Kalimantan, Indonesia - Yui Hashimoto; Fathul Yusro; Yeni Mariani; Farah Diba; Kazuhiro Ohtani (Wood Research Journal, 2019)
Study for local knowledge about ethnopharmacology especially medicinal plants used by the community is still limited. West Kalimantan possess a tropical rain forest with megabiodiversity. One of the areas where Malay and Dayak people use medicinal plants from the forest is Sekabuk village, Sadaniang Subdistrict, Mempawah District of West Kalimantan,  Indonesia. This research has two objectives: first, to summarize the local knowledge of medicinal plants in the Sekabuk village, and second to identify the the mechanisms of shared on knowledge on used the medicinal plants on each ethnic. The research was conducted by in-depth interview and survey for 45 days in the village. The research programme consisted of interviews, plant observations, and a collection of medicinal plants from five different subdistricts sites i.e. Gelombang, Malangga, Pak Nungkat, Sekabuk, and Titi Dahan. The whole plants, part(s) used, and remedy formulations were elicited from healers and voucher specimens were collected for identification and stored at Forestry Faculty, Tanjungpura University. The results showed that there are 66 plants used for medicine. The family of plants consisted of Zingiberaceae, Lamiaceae abd Mrytaceae. The leaves  were most frequently used (108), followed by roots (47), whole plant (21), top (6), stems and fruits (5), and sap (1). The methods for preparation and administration and the awareness of medicinal plants are different by ethnic groups and the living environments. The difference between the genders did not significant in terms of knowledge about medicinal plants. Meanwhile, A retention of traditional knowledge of medicinal plants was significant in rural of West Kalimantan. The plants used as medicine were clearly different by ethnic groups, Malay and Dayak. The living environments also affect the difference of used plants on basis of plants accesibility.